Risk for Cardiovascular Death Associated With Waist Circumference and Diabetes: A 9-Year Prospective Study in the Wan Shou Lu Cohort - Li, Man; Zhu, Ping; Wang, Shu-xia (Frontiers in Cardiovascular Medicine, 2022)
Background: It has been reported that obesity and diabetes are both the risk factors for the development of cardiovascular diseases (CVD). However, recent articles reported that compared with BMI, waist circumference (WC) can better reflect obesity, more closely related to visceral fat tissue which is positively associated with an increased risk of cardiovascular death. Moreover, few studies have investigated the prognostic value of both WC and diabetes during a long-term follow up. We aimed to investigate whether higher level of WC measurements and diabetes were able to predict cardiovascular mortality in general population. Methods: In this prospective cohort study, a total of 1521 consecutive subjects free of clinical cardiovascular disease were included. The end point was cardiovascular death. The Kaplan-Meier method and Cox regression models were used to evaluate the cumulative risk of outcome at different WC levels with or without diabetes. Results: During a median follow up of 9.2 years, there were 265 patients had the occurrence of cardiovascular death. Kaplan-Meier survival estimates indicated that the patients with higher levels of WC (WC>94cm) coexist with diabetes had significantly increased risk of cardiovascular death (log-rank p＜0.05). After adjustment for potential confounders, multiple COX regression models showed that the incidence of cardiovascular death was significantly higher when patients with high WC coexisted with DM (HR 3.78; 95% CI: 3.35–3.98; p＜0.001). Conclusion: Patients with high WC and diabetes represent a high-risk population for cardiovascular death. WC and diabetes may provide incremental prognostic value beyond traditional risks factors